Effects of partial replacement of corn by bakery waste in the diet on performance of Holstein steers - Passini, Roberta; Spers, Aleksands; Lucci, Carlos de Sousa (Pesquisa Agropecuaria Brasileira, 2001)
The effects of addition of bakery waste (BW) replacing corn in the diet of Holstein steers were studied. Four treatments, respectively to the addition of 0%, 10%, 20% and 30% of bakery waste were applied in the concentrated mixture for corn replacement. Animals were fed with complete mixtures pelleted ration, with 30% of Coast-cross hay (Cynodon dactylon L.) as roughage. The experimental design was in randomized blocks, with four treatments and five repetitions, totalizing 20 animals. The performance was evaluated by intake and feed conversion, weight gain, heart-girth and size. Diarrhea incidence was evaluated through daily observation of faeces. The experiment began when calves reached 90 kg of life weight, and lasted for 120 days. The results did not show statistically significant differences among treatments concerning weight gain, dry matter intake, feed conversion, heart-girth, height at whiter and diarrhea incidence. The addition of bakery waste caused feed costs reduction of 3.74%, 7.44% and 10.90% respectively for 10%, 20% and 30% of bakery waste, in comparison to the control diet (0%). So, bakery waste is an alternative source for feeding and for reduction of costs of growing steers, in comparison to corn.